Inner filter effect-based upconversion fluorescence sensing of sulfide ions. Issue 37 (5th September 2022) - Sun, Lanjuan; Sun, Chunning; Ge, Yang; Zhang, Zhaoming; Zhou, Jiancheng
Abstract : Inner filter effect-based upconversion nanoprobes were developed by the combination of core-shell-structured upconversion nanoparticles and copper-based chelates, exhibiting excellent sensing of sulfide ions with high sensitivity and selectivity. Abstract : Upconversion nanocrystals (UCNCs) have emerged as a new type of fluorescent probe for sensing applications. Herein, we designed a 980 nm excited upconversion luminescence system, composed of core–shell-structured NaYF4  : Yb, Er@NaYF4  : Yb nanocrystals (csUCNCs) and the triethylenetetramine–Cu complex (complex-I), for quantitative detection of sulfide ions. Taking advantage of the specific recognition of complex-I toward S 2−, the as-formed compound (complex-II) exhibits excellent spectral overlap not only in the range of fluorescence emissions of UCNCs but also in the excitation wavelength for UCNCs; fluorescence quenching of UCNCs occurs where the complex-II acts as the energy acceptor. Due to the electrostatic repulsion between positively charged ligand-free csUCNCs and complex-I, the fluorescence quenching is based on the primary and secondary inner filter effect rather than the fluorescence resonance energy transfer process. The detection limit of S 2− for the upconversion-based system is calculated to be 2.7 μM, exhibiting higher detection sensitivity over the single complex-I compound measured by the spectrophotometric method. Moreover, no significant variation in upconversion luminescence is observed upon the addition of other interfering ions, showing the excellent selectivity of this nanoprobe toward S 2− .